Comparative Evaluation of (18F)AlF-PSMA-HBED-CC and 68Ga-PSMA-HBED-CC in Staging Intermediate-/High-Risk Prostate Cancer: A Prospective Study - dos Santos Loureiro, Gerardo Gabriel; Duarte Couto, Pablo; Gambini Gonzalez, Juan Pablo; Alonso Nuñez, Omar (World Journal of Nuclear Medicine, 2025)
Objective 68Ga-PSMA-HBED-CC positron emission tomography (PET)/computed tomography (CT) represents a clinically relevant technique for the evaluation of prostate cancer (PCa) patients, whereas 18F-AIF-PSMA-HBED-CC is a novel tracer produced in our center, with suitable radiochemical purity for clinical purposes. We prospectively compared the diagnostic values of both tracers for the detection of metastatic disease in patients with intermediate-/high-risk PCa at initial staging.Materials and Methods Sixty-six patients (mean age: 63 years; range: 52–78 years) with PCa at initial staging (Gleason score ≥6; median prostate-specific antigen [PSA]: 10 ng/mL; range:1.7–152 ng/mL) prospectively underwent routine 68Ga-PSMA-11 and 18F-AlF-PSMA-11 PET/CT scanning with a 64-slice PET/CT scan with time-of-flight (TOF) correction. We measured the maximum standardized uptake value (SUVmax) and lesion-to-background ratio (LBR) in all coincidentally detected lesions. Open prostatectomy and pelvic lymph node dissection were performed in nonmetastatic patients. Histopathology, correlative imaging, and/or clinical follow-up were considered the gold standard. Follow-up was conducted at least 4 months after PET/CT scanning (median: 6.4 months; range: 4–11 months). Sensitivity, specificity, and predictive values were calculated.Results The overall detection rate was 85% (56/66) for both tracers. At least one suspicious lesion indicating potential PCa metastasis was detected in 20 (30%) and 21 (32%) of 66 patients for 68Ga-PSMA-11 and 18F-AIF-PSMA-11 tracers, respectively. A total of 145 extra-prostatic lesions were detected in the bone (n = 56), lymph nodes (n = 88), and lung (n = 1) by at least one radiopharmaceutical: 131 (90%) for 68Ga-PSMA-11 and 123 (85%) for 18F-AlF-PSMA-11.In concordant lesions, a significant correlation was found between the SUVmax of both tracers (r = 0.90, p = 0.001). The SUVmax and LBR for 18F-AlF-PSMA-11 were higher in bone foci (n = 39) compared with 68Ga-PSMA-11 (7.2 vs. 8.9 and 14 vs. 13, respectively, p = 0.02).For the detection of systemic metastasis, the sensitivity values were the same for both techniques: 0.90 (95% confidence interval [CI]: 0.68–0.98). We calculated specificities of 0.96 (95% CI: 0.85–0.99) and 0.94 (95% CI: 0.82–0.98) for 68Ga-PSMA-11 and 18F-AlF-PSMA-11, respectively.Conclusions 68Ga-PSMA-11 and 18F-AlF-PSMA-11 PET/CT seem to be clinically equivalent imaging techniques for the assessment of primary intermediate-/high-risk PCa with promising potential for the detection of metastatic spread that would impact patient management.
Keywords: high-risk prostate cancer; initial staging; 18F-AlF-PSMA-11; 68Ga-PSMA-11; PET/CT